Recenzja: Karin Friedrich, The Other Prussia. Royal Prussia, Poland and Liberty, 1569-1772, Cambridge University Press, 2000, ss. 280. - Dariusz Makiłła (Czasopismo Prawno-Historyczne)
Karin Friedrich, The Other Prussia. Royal Prussia, Poland and Liberty, 1569-1772, Cambridge University Press, 2000, ss. 280.